The Effects of Total Health Expenditure on Economic Growth in Central and Eastern Sub-Sahara African Regions - Faith Yusufu; Olanike Bosede Awoyemi; Kehinde John Komolafe (International Journal of Economics Development Research (IJEDR), 2022)
This study looked at the link connecting the growth of the economy and health spending in Central and Eastern Sub-Saharan Africa. To assess the short and long-term effects of total per capita health expenditure on the growth of the economy across Sub-Saharan African areas (East Africa and Central Africa), the panel data analysis was employed. In the short-term, total per-capita health expenditure (THE_PC) in Central Africa has an upbeat outcome on economic growth (LGDP_PC) at all levels of significance. In the long-term, current health per-capital expenditure (CHE_PC) has an upbeat outcome on the growth of the economy (LGDP_PC) at 5% and 10% significance levels, whereas life expectancy at birth (LEB) has a downbeat outcome on the growth of the economy. In East Africa THE_PC in the short and long-run has a favorable effect on the growth of the economy (LGDP_PC) at 5 and 10% significant levels, whereas CHE_GDP has a downbeat outcome on the growth of the economy (LGDP_PC) at all levels in the long-run. The findings imply that increasing per-capita health spending will boost the growth of the economy in the short term while increasing CHE_PC and LEB will boost economic growth in the long run. More investment in health services is recommended. Keywords: Public Spending, Economic Growth, GDP Per-Capita, Long Run, Mean Group, Dynamic Fixed Effect, Pooled Mean Group/ARDL (Autoregressive Distributed Lags), Short Run